(untitled) (TAMADDUN NURI JURNALI, 2025)
This study is devoted to the analysis of the semantic and structural characteristics of lexical units that reflect national mentality in the Uzbek and Karakalpak languages. The article explores the semantic fields of words associated with deeply rooted national values, customs, religious beliefs, and social relationships in the collective consciousness. Using comparative linguistic methods, the research identifies the common and unique features of lexical units present in both languages.